1987
DOI: 10.1089/cdd.1987.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Doxorubicin and Cisplatin on Multicellular Tumor Spheroids from Human Lung Cancer

Abstract: We tested the sensitivity to doxorubicin (DXR) and cisplatin (DDP) of multicellular tumor spheroids (MTS) developed from 2 human lung cancer cell lines; PC-10 squamous cell carcinoma and PC-6 small cell carcinoma. DDP was able to maintain its efficacy in MTS: PC-10 MTS were only 3-fold more resistant to DDP than in monolayer and in PC-6 cells DDP induced cell lethality was essentially unchanged irrespective of cells being in a monolayer or MTS. Atomic absorption spectrometry revealed that DDP uptake was essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Because 3D multicellular tumor spheroids provide a microenvironment that mimics tumors in vivo, (10) spheroid culture has been used to evaluate tumor cell invasiveness and ⁄ or its responsiveness to anticancer drugs. (11)(12)(13)(14)(15) At IC 10 determined in monolayer culture, both cisplatin or docetaxel did not affect filopodia formation. However, at IC 50 also determined in monolayer culture, docetaxel, but not cisplatin, significantly decreased filopodia formation in HEp-2 cells in spheroid culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because 3D multicellular tumor spheroids provide a microenvironment that mimics tumors in vivo, (10) spheroid culture has been used to evaluate tumor cell invasiveness and ⁄ or its responsiveness to anticancer drugs. (11)(12)(13)(14)(15) At IC 10 determined in monolayer culture, both cisplatin or docetaxel did not affect filopodia formation. However, at IC 50 also determined in monolayer culture, docetaxel, but not cisplatin, significantly decreased filopodia formation in HEp-2 cells in spheroid culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance of MTS to drugs such as DXR (9), methotrexate (10) and bleomycin or peplomycin (11) have been reported to be due mainly to impaired penetration of the drug. Previous work from our laboratory revealed that patterns of DXR-induced cell lethality and the drug penetration depended on tumor cell types (12). Thus, PC-10 human squamous cell carcinoma MTS were progressively more resistant to DXR when their size increased, whereas the susceptibility of PC-6 human small cell carcinoma MTS tended to increase when the MTS grew larger.…”
Section: Introductionmentioning
confidence: 83%
“…The population doubling time of PC-6 cells was approximately 20 hrs and that of PC-10 cells was 23 hrs. MTS production MTS were produced by the method described by Yuhas et al (1,2) with minor modifications (12). One x 105 viable PC-6 or PC-10 cells in 10 ml of the complete medium were placed in 100 mm plastic Petri dishes (No.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The positive inoculum effect shown in DXR-induced tumor cell kill resulted from lessened cellular accumulation of the drug at high cell densities rather than drug inactivation. 5,6 This phenomenon (posi tive inoculum effect) was originally demonstrated in certain antimicrobial antibiotics of which the inhibitory concentrations in vitro were influenced by the inoculum size of some microbial organisms. 7,8 In experimental animal tumor systems, a remarkable therapeutic synergism was observed in the administration of DXR in combination with CDDP against advanced P388 leukemia and Ridgway osteogenic sarcoma9 as well as Sarcoma 180.10 Combination chemotherapy of these two drugs had marked therapeutic potentiation against ovarian carcinoma and other cancer in man.11 -13 We hypothesized that if DXR is less active at high tumor cell densities and the antitumor effect of CDDP is not influenced by cell density, the proper sequence of administration should be CDDP first followed by DXR, rather than simultaneous exposure or reversed order of the combination.…”
Section: Introductionmentioning
confidence: 98%